Physical Therapist Management of Parkinson Disease: A Clinical Practice Guideline From the American Physical Therapy Association. Issue 4 (28th December 2021) - Osborne, Jacqueline A; Botkin, Rachel; Colon-Semenza, Cristina; DeAngelis, Tamara R; Gallardo, Oscar G; Kosakowski, Heidi; Martello, Justin; Pradhan, Sujata; Rafferty, Miriam; Readinger, Janet L; Whitt, Abigail L; Ellis, Terry D
Abstract: A clinical practice guideline on Parkinson disease was developed by an American Physical Therapy Association volunteer guideline development group that consisted of physical therapists and a neurologist. The guideline was based on systematic reviews of current scientific and clinical information and accepted approaches for management of Parkinson disease. The Spanish version of this clinical practice guideline is available as a supplement (Suppl. Appendix 1 ).